Pemahaman Teologis Tentang Karunia Roh Kudus dalam 1 Korintus 12:4-11 : Perspektif Alkitabiah Dan Aplikasinya - Arismawati Halawa; Malik Bambangan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the theological understanding of the gifts of the Holy Spirit in 1 Corinthians 12:4-11, and its impact on the life of faith of Christians. The Apostle Paul emphasized the diversity of the gifts of the Holy Spirit given to every believer to build the body of Christ, namely the church. Although there are many different gifts, all come from one source, namely the Holy Spirit, and are intended for the common good. The theological view of Randy Frank Rouw highlights the important role of the Holy Spirit in the missionary service of the church, which enables people to sincerely accept Jesus and live His truth. This study uses a qualitative approach with a descriptive-analytical method to examine the understanding of the gifts of the Holy Spirit and its relevance in the context of the contemporary church. Data were obtained through a literature study with content analysis using the hermeneutic method, which provides an in-depth understanding of the meaning of these gifts in the historical and cultural context of the Corinthian congregation. The study also discusses how the modern church can apply these gifts wisely, considering the challenges faced by the contemporary church, such as differences in theological views and individualism. The results of the study emphasize the importance of a correct understanding of the gifts of the Holy Spirit in the life of the church today, with the aim of introducing Jesus Christ to the world and glorifying God. The diversity of gifts must be appreciated in the unity of the body of Christ, and each congregation is expected to use these gifts in love, complementing each other, and supporting the development of the church and society. This approach aims to provide practical guidance for the church in implementing the biblical teachings on the gifts of the Holy Spirit.